Cultural and linguistic diversity of people living with chronic hepatitis B in 2011-2016: changing migration, shifting epidemiology - Jennifer H. MacLachlan; Benjamin C. Cowie (Elsevier, 2018)
Abstract Objective: To estimate the cultural and linguistic diversity in Australians currently living with chronic hepatitis B (CHB), the majority of whom were born overseas, and to identify trends in this diversity over time. Methods: Estimates were generated by combining Australian census country of birth information with seroprevalence data generated from antenatal serology linked with surveillance notifications. The number of people living with CHB was assessed according to country of birth using the 2011 and 2016 censuses. Results: The total number of Australian residents living with CHB increased by 20% between 2011 and 2016, substantially outpacing population growth. The most common country of birth continued to be China, with the number of Chinese‐born Australians living with CHB increasing by 60% in the 5‐year period. Decreased numbers were observed for people born in European countries. Conclusions: The epidemiology of chronic hepatitis B in Australia has shifted over time due to changing migration patterns, with increases in many countries in the Asia‐Pacific, African and Middle Eastern regions. Implications for public health: Interventions to improve the health of people living with CHB are imperative, and these up‐to‐date estimates identify priority groups and communities, which are constantly changing.